Peran Dukungan Keluarga terhadap Aktivitas Fisik dan Tingkat Depresi pada Pasien Stroke Non Hemoragik - Lusiawati Lusiawati; Andi Rahmaniar; Ita Rini; Yonathan Ramba (TIN: Terapan Informatika Nusantara, 2026)
Non-hemorrhagic stroke often leads to limitations in physical activity and psychological problems such as depression, which may affect the recovery process. Family support is known to play an important role in helping patients adapt to these conditions; however, evidence regarding the relationship between family support, physical activity, and depression in local healthcare settings remains limited, particularly at the Tidore Islands Regional Hospital. This study aimed to analyze the relationship between family support and both physical activity and depression levels in patients with non-hemorrhagic stroke. A quantitative correlational study with a cross-sectional approach was conducted involving 70 respondents selected through purposive sampling. Data were collected using a family support questionnaire, the Barthel Index for physical activity, and the Geriatric Depression Scale for depression level, and were analyzed using Pearson correlation tests. The results showed a significant relationship between family support and physical activity (p < 0.05; r = …), as well as a significant relationship between family support and depression level (p < 0.05; r = …). The direction of the correlations indicates that higher family support is associated with better physical activity and lower levels of depression. These findings highlight the important role of family involvement in supporting both physical and psychological recovery among stroke patients. Therefore, healthcare providers, particularly nurses and physiotherapists, are encouraged to integrate family-based approaches into rehabilitation programs to improve patient independence and overall well-being.